The Use of Extensive Reading to Enhance Students' Vocabulary Mastery - Syahril, Syahril; Samtidar, Samtidar; Muliati, A. (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study aims to determine whether or not extensive reading can enhance students' vocabulary mastery at SMA Negeri 4 Sidrap. The research investigates how whether exposure to diverse texts aids in learning new words, improves retention, and enhances overall vocabulary skills. A quantitative approach with a pre-experimental design, specifically a one-group pre-test and post-test method, was employed. The sample comprised 22 second-grade senior high school students from one class. Over four meetings, the students underwent treatments focused on vocabulary mastery, which involved receiving material from the researchers and engaging in reading comprehension activities. These activities included reading a passage, writing a reading report, discussing the text, and retelling what they had read. Data collection was conducted through pre-tests and post-tests administered after the treatment. The study's results indicated that extensive reading is significantly effective in enhancing students' vocabulary mastery. The data showed an improvement in students' scores from the pre-test to the post-test, with the mean pre-test scores indicating a low level of vocabulary mastery and the mean post-test scores indicating a satisfactory level of vocabulary mastery. In conclusion, the study demonstrates that extensive reading effectively enhances students' vocabulary mastery at SMA Negeri 4 Sidrap.